Orientations and capabilities of born global firms from emerging markets. Issue 6 (12th November 2018) - Falahat, Mohammad; Knight, Gary; Alon, Ilan
Abstract : Purpose: The purpose of this paper is to examine the impact of entrepreneurial orientation and networking capabilities of born global firms in an emerging market on marketing strategy and foreign market performance. Design/methodology/approach: Structural equation modeling was used to analyze data from 1, 001 internationalized firms in an emerging market and to test seven hypotheses regarding the development of marketing strategy and foreign market performance. Findings: Marketing strategy was found to mediate the relationship between entrepreneurial orientation and networking capability and foreign market performance, while foreign market performance is affected by entrepreneurial orientation and marketing strategy. Research limitations/implications: Research on emerging market multinationals can be merged with that of born globals to augment our understanding of how early internationalizers from emerging markets perform in foreign markets. Originality/value: This study is among the few focusing on born globals in emerging markets, which face the difficulties of newness and limited resources, as well as characteristics of emerging markets, such as institutional voids.